Revisiting the L-Dopa Response as a Predictor of Motor Outcomes After Deep Brain Stimulation in Parkinson’s Disease - Lin, Zhengyu; Zhang, Xiaoxiao; Wang, Linbin; Zhang, Yingying; Zhou, Haiyan; Sun, Qingfang; Sun, Bomin; Huang, Peng; Li, Dianyou (Frontiers in Human Neuroscience, 2021)
Objective To investigate the correlation between preoperative response to the L-dopa challenge test and efficacy of deep brain stimulation (DBS) on motor function in Parkinson’s disease (PD). Methods We retrospectively reviewed the data of 38 patients with idiopathic PD who underwent DBS surgery with a median follow-up duration of 7 months. Twenty underwent bilateral globus pallidus interna (GPi) DBS, and eighteen underwent bilateral subthalamic nucleus (STN) DBS. The Movement Disorder Society Unified Parkinson Disease Rating Scale-Motor Part (MDS UPDRS-III) was assessed before surgery and at the last follow-up in different medication and stimulation conditions, respectively. Results Pearson’s correlation analysis revealed a positive correlation between preoperative L-dopa challenge responsiveness and GPi-DBS responsiveness on the total score (R²= 0.283, p = 0.016) but not on the non-tremor total score (R² = 0.158, p = 0.083) of MDS UPDRS-III. Such correlation remained significant (R²’ = 0.332, p = 0.010) after controlling for age at the time of surgery as confounding factor by partial correlation analysis. The preoperative L-dopa challenge responsiveness was significantly correlated with the tremor-controlling outcome of GPi-DBS (R² = 0.390, p = 0.003). In contrast, we found a positive correlation between preoperative L-dopa challenge responsiveness and STN-DBS responsiveness on the non-tremor total score (R² = 0.290, p = 0.021), but not on the total score (R² = 0.130, p = 0.141) of MDS UPDRS-III. The partial correlation analysis further demonstrated that the predictive value of preoperative L-dopa challenge responsiveness on the non-tremor motor outcome of STN-DBS was eliminated (R²’ = 0.120, p = 0.174) after controlling for age at the time of surgery as confounding factor. Interpretation The short-term predictive value of preoperative response to the L-dopa challenge test for the motor outcome of GPi-DBS in PD was systematically described. Our findings suggest: (1) a solid therapeutic effect of GPi-DBS in treating L-dopa-responsive tremors; (2) a negative effect of age at the time of surgery on motor outcomes of STN-DBS, (3) a possible preference of STN- to GPi-DBS in L-dopa-resistant tremor control, and (4) a possible preference of GPi- to STN-DBS in elderly PD patients who have a satisfactory dopamine response.